Insights into the palaeobiology of sauropodomorph dinosaurs through an analysis of their bone histology - Toefy, Mohammed Fay-yaad (Department of Biological Sciences, 2025)
The Elliot Formation (EF) of Southern Africa ranges from the Late Triassic to Early Jurassic. Many sauropodomorph dinosaurs such as Massospondylus, Melanorosaurus and Antetonitrus have been excavated from the EF. These dinosaurs range from basal Sauropodomorpha to the derived Sauropodiformes providing key insight into their evolution. Osteohistology studies are well recognised as providing much biological information about the growth dynamics of extinct animals, and several studies have focused on either basal Sauropodomorpha or derived Sauropoda. This research assesses the osteohistology of one basal Sauropodomorpha, Plateosauravus as well as three derived Sauropodiformes, Sauropodiforme indet., Melanorosaurus and Lessemsauridae indet. to better understand their growth dynamics of the transitionary Sauropodiformes en route to Sauropoda. Preparation and analysis of thin sections were undertaken on primarily long bones of Plateosauravus (SAM-PK-2780 – 3603), Sauropodiforme indet. (NMQR-3314), Melanorosaurus (NMQR-1551) and Lessemsauridae indet., (SAM-PK-K382). Histological descriptions and comparisons were completed within and between taxa. The general histology of all long bones was similar. In early to mid-stages of the ontogeny, fibrolamellar bone was the dominant bone type followed by parallel fibred bone in late stages of ontogeny. Melanorosaurus elements differed by exhibiting a distinctive periosteal pathology and considerably more secondary remodelling in the femur. Although badly fragmented, Sauropodiforme indet. elements show similar histological features. Both Plateosauravus and Lessemsauridae indet. differ primarily in the degree of vascularisation around LAGs and secondary reconstruction. The number of growth marks varied between two to three in the fragmented Sauropodiforme indet., five to six in Melanorosaurus and Plateosauravus and up to ten in Lessemsauridae indet. LAGs in the basal taxon, Plateosauravus, were found throughout the compacta while the derived Sauropodiformes taxa primarily had growth marks in the outer half. The delayed deposition of LAGs differed between basal Sauropodomorpha and Sauropodiformes thus suggesting shifts towards more uninterrupted growth. Overall, the growth dynamics of these Sauropodomorph dinosaurs suggest an increase in growth rates and shift towards rapid, sustained growth as seen in the more derived Sauropoda, although they also show some variation in their individual growth dynamics.